Aerobic With Resistance Training or Aerobic Training Alone Poststroke: A Secondary Analysis From a Randomized Clinical Trial. (March 2018) - Marzolini, Susan; Brooks, Dina; Oh, Paul; Jagroop, David; MacIntosh, Bradley J.; Anderson, Nicole D.; Alter, David; Corbett, Dale
Background: Stroke is associated with muscle atrophy and weakness, mobility deficits, and cardiorespiratory deconditioning. Aerobic and resistance training (AT and RT) each have the potential to improve deficits, yet there is limited evidence on the utility of combined training.Objective : To examine the effects of AT+RT versus AT on physiological outcomes in chronic stroke with motor impairments.Methods: Participants (n = 73) were randomized to 6 months of AT (5 d/wk) or AT+RT (3 and 2 d/wk, respectively). Outcomes included those related to body composition by dual-energy X-ray absorptiometry, mobility (6-minute walk distance [6MWD], sit-to-stand, and stair climb performance), cardiorespiratory fitness (VO2peak, oxygen uptake at the ventilatory threshold [VO2VT ]), and muscular strength.Results: A total of 68 (93.2%) participants (age, mean ± SD = 63.7 ± 11.9) completed the study. AT+RT and AT yielded similar and significant improvements in 6MWD (39.9 ± 55.6 vs 36.5 ± 63.7 m, P = .8), VO2peak (16.4% ± 43.8% vs 15.2% ± 24.7%, P = .9), sit-to-stand time (−2.3 ± 5.1 vs 1.02 ± 9.5 s, P = .05), and stair climb performance (8.2% ± 19.6% vs 7.5% ± 23%, P = .97), respectively. AT+RT produced greater improvements than AT alone for total body lean mass (1.23 ± 2.3 vs 0.27 ± 1.6 kg, P = .039), predominantly trunk ( P = .02) and affected-side limbs ( P = .04), VO2VT (19.1% ± 26.8% vs 10.5% ± 28.9%, P = .046), and upper- and lower-limb muscular strength ( P < .03, all except affected-side leg).Conclusion: Despite being prescribed 40% less AT, AT+RT resulted in similar and significant improvement in mobility and VO2peak, superior improvements in VO2VT and muscular strength, and an almost 5-fold greater increase in lean mass compared with AT. RT is the most neglected exercise component following stroke but should be prescribed with AT for metabolic, cardiorespiratory, and strength recovery.